Anthracnose severity in F2 lima bean progenies obtained by hybridization without emasculation - Brito, Marilha Vieira de (2025)
The objective of this study was to obtain anthracnose-resistant lima bean progeny by artificial hybridization. The study was conducted at the Agricultural Sciences Center of the Federal University of Piauí (UFPI), Teresina – Piauí. For the F2 phytopathological evaluation experiment, a completely randomized experimental design was used with four replicates per progeny and a plot consisting of one plant. For inoculation, the CT4 isolate of Colletotrichum truncatum was used at 106 spores/mL, and a control plant was inoculated with autoclaved distilled water. Ten trifoliate leaves of each genotype were scanned from the intermediate region of the plant using ASSES 2.0. After assessing the severity, the average ratings for each population were calculated, classifying them into five categories according to the resistance. To conduct the analysis of variance, the severity data were transformed by and grouped by the test proposed by Scott and Knott (P < 0.05). All analyses were performed using the R and GENES programs. Seven days after inoculation, the progênies were divided into three groups. Groups “A” and “B” corresponded to genotypes classified as highly susceptible and group “C” to genotypes classified as moderately resistant and highly resistant. The genotypes BGP-UFPI 220, BGP-UFPI 251, BGP-UFPI 798, BGP-UFPI 832, BGP-UFPI 1000, and BGP-UFPI 1002 can be used as parents in lima bean improvement programs. Progenies that were moderately resistant and highly resistant, totaling sixteen, were selected for use in breeding programs aimed at anthracnose resistance.